INFLUENCE OF GADGET USAGE AND PARENT INVOLVEMENT TO CHILDRENS PROSOCIAL BEHAVIOR - LAINI, ALIF (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
This expo facto research aims to see the effect of gadget usage and parent involvement on child prosocial behavior with sample of 80 parent of child. This research was done by data collecting technique used in research using questionnaire on each variable X1, X2 and Y. In variable X1 (use of gadget) while variable X2 (parent involvement) and for variable Y (prosocial behavior). Data analysis technique in this research is quantitative data analysis. The results show that overall the level of prosocial behavior of low gadget usage (A2) is higher than the use of high gadget (A1), there is an interaction between the use of gadgets with parental involvement on childs prosocial behavior, there is a difference in behavioral level prosocial use of low gadget (A2) parental involvement high (B1) higher than high prosocial use behavior (A1) high parental involvement (B1), there is a difference in behavior level prosocous low use gadget (A2) high parental involvement (B1) higher than prosocial behavior of low gadget usage (A2) low parental involvement (B1).